2020
DOI: 10.1186/s12943-020-1137-5
|View full text |Cite
|
Sign up to set email alerts
|

DNA-methylation-mediated activating of lncRNA SNHG12 promotes temozolomide resistance in glioblastoma

Abstract: Background: Accumulating evidence shows that long noncoding RNAs (lncRNAs) are important regulator molecules involved in diverse biological processes. Acquired drug resistance is a major challenge in the clinical treatment of glioblastoma (GBM), and lncRNAs have been shown to play a role in chemotherapy resistance. However, the underlying mechanisms by which lncRNA mediates TMZ resistance in GBM remain poorly characterized. Methods: Quantitative reverse transcription PCR (qRT-PCR) and fluorescence in situ hybr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
127
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(142 citation statements)
references
References 50 publications
2
127
0
Order By: Relevance
“…According to previous studies, abnormally high expression of lncRNA may be induced by transcription activators, stress, DNA methylation, and exosomes [47][48][49][50][51]. For example, the tumor suppressor gene p53 can transcriptionally activate lncRNA Pvt1b [47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to previous studies, abnormally high expression of lncRNA may be induced by transcription activators, stress, DNA methylation, and exosomes [47][48][49][50][51]. For example, the tumor suppressor gene p53 can transcriptionally activate lncRNA Pvt1b [47].…”
Section: Discussionmentioning
confidence: 99%
“…Stress-induced lncRNA LASTR is up-regulated in hypoxic breast cancer [49]. Upregulation of lncRNA SNHG12, mediated by DNA methylation, thereby activating and increasing temozolomide resistance in glioblastoma [50]. Exosome-mediated lncRNA AFAP1-AS1 activates ERBB2 translation [51].…”
Section: Discussionmentioning
confidence: 99%
“…Glioblastoma has been identified as a highly infiltrative brain tumor and difficult to cure. 27 Currently, emerging reports have demonstrated the significance of lncRNAs in the tumorigenesis. Using the sequencing technology, a large number of cancer-related lncRNAs have been found.…”
Section: Discussionmentioning
confidence: 99%
“…Belter et al [31] observed a global DNA hypomethylation in the range of therapeutically achieved TMZ concentrations over longer exposure times. Lu et al [38] report that the hypomethylation of promoter region of SNHG12 occurs in TMZ-resistant cells and that this contributed to lnc-RNA-SNHG12 activation resulting in TMZ resistance. Thus, TMZ effect on DNA methylation could be responsible for the increase expression of MGMT in GBM.…”
Section: Mechanisms Of Resistance Specific To Tmzmentioning
confidence: 99%